Analysis of the USM Lecturer PPKM application portal using COBIT 2019 Framework - nuranto, bogo; Hartomo, Kristoko Dwi; wahyono, Teguh (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2024)
The USM lecturer PPKM application portal information system provides services and information regarding the research and community service activities of USM lecturers. The services available in this application include PPKM proposals, PPKM assessments, PPKM evaluations, progress reports, contracts, assignment letters and presentation schedules. To improve the system services that have been used so far, analysis and evaluation are needed so that system performance can provide accurate information and according to needs. The purpose of this research is to analyze the performance of applications using the COBIT 2019 framework. The method used is a mix method, which combines data from interviews and observations and data from questionnaires. The research subjects consisted of 7 (seven) IT admins and 30 USM permanent lecturers. The COBIT 2019 framework used as the basis for analysis consists of 11 factors, namely:  Enterprise strategy; Enterprise goals; Risk Profile; IT Related Issue; IT Threat Landscape; Compliance Requirement; Role Of IT; IT Sourcing Model; IT Implementation Method; Technology Adaptation Strategy; and Enterprise Strategy. The results showed that there are 2 (two) objectives that need to go to the core model evaluation stage, namely BAI03 and BAI07. The results of the maturity analysis on BAI03 are at level 2, which is 67.1%. While the results of the maturity analysis on BAI07 show results of 72.7%.